Improvement in High-Grade Osteosarcoma Survival: Results from 202 Patients Treated at a Single Institution in Taiwan. Issue 15 (April 2016) - Hung, Giun-Yi; Yen, Hsiu-Ju; Yen, Chueh-Chuan; Wu, Po-Kuei; Chen, Cheng-Fong; Chen, Paul C-H; Wu, Hung-Ta H.; Chiou, Hong-Jen; Chen, Wei-Ming
Abstract : Abstract: The aim of this study was to compare survival before and after 2004 and define the prognostic factors for high-grade osteosarcomas beyond those of typical young patients with localized extremity disease. Few studies have reported the long-term treatment outcomes of high-grade osteosarcoma in Taiwan. A total of 202 patients with primary high-grade osteosarcoma who received primary chemotherapy at Taipei Veterans General Hospital between January 1995 and December 2011 were retrospectively evaluated and compared by period (1995–2003 vs 2004–2011). Patients of all ages and tumor sites and those following or not following controlled protocols were included in analysis of demographic, tumor-related, and treatment-related variables and survival. Overall survival and progression-free survival at 5 years were, respectively, 67.7% and 48% for all patients (n = 202), 77.3% and 57.1% for patients without metastasis (n = 157), and 33.9% and 14.8% for patients with metastasis (n = 45). The survival rates of patients treated after 2004 were significantly higher (by 13%–16%) compared with those of patients treated before 2004, with an accompanying 30% increase in histological good response rate ( P  = .002). Factors significantly contributing to inferior survival in univariate and multivariate analyses were diagnosis before 2004, metastasis at diagnosis, and being a noncandidate for a controlled treatment protocol. By comparison with the regimens used at our institution before 2004, the current results support the effectiveness of the post-2004 regimens, which consisted of substantially reduced cycles of high-dose methotrexate and a higher dosage of ifosfamide per cycle, cisplatin, and doxorubicin, for treating high-grade osteosarcoma in Asian patients.